Analysis of United States Involvement in the Palestine and Israel Conflicts - Weilan Aksendi (Indonesian Journal of Peace and Security Studies (IJPSS), 2021)
The purpose of this research is to outline the United States' national interest in recognizing Jerusalem as Israel's capital, as well as the consequences of doing so. The qualitative research approach was applied. The majority of the data was gathered through book research, observation, documentation, and internet data searches. According to the study's findings, the United States' recognition is an endeavor to serve its country's national interests, which has influenced ties between the two nations, which have grown closer since the recognition